Validity and reliability of Nine Types Temperament Scale - Yılmaz, Enver Demirel; Gençer, Ali Görkem; Aydemir, Ömer; Yılmaz, Ayşe; Kesebir, Sermin; Ünal, Özge; Örek, Alp; Bilici, Mustafa (Turkish Education Association, 2014)
The aim of this study is to develop a scale compatible with the Nine Types Temperament Model (NTTM), which did not have any prior measurement tools to scientifically prove its reliability and validity. NTTM is created by re-evaluating the Enneagram System-a system that defines nine personality types- used for analyzing and comprehending ego mechanisms. Nine Types Temperament Scale (NTTS) which is a self-rated instrument composed of 91 items with three-point Likert type was developed from this model and applied to 990 participants. Confirmatory factor analyses were carried out in order to evaluate whether the scale fits to the model related to the temperament model. In exploratory factor analyses of the scale eigen values of nine factors vary between 8.089 and 1.661, and represent 39.04% of the total variance. In confirmatory analyses of the scale CFI value is 0.88, GFI value is 0.84, IFI value is 0.88 and RMSEA value is 0.05. Test-retest reliability of the scale was evaluated with 46 participants. Cronbach alpha value of the whole scale is 0.75, while Cronbach alpha values for every temperament type were calculated as 0.77, 0.79, 0.68, 0.71, 0.80, 0.74, 0.71, 0.83 and 0.77 respectively. Concurrent validity was performed with Cloninger's TCI (Temperament and Character Inventory) and Akiskal's TEMPS-A (Temperament Evaluation of Memphis, Pisa, Paris and San Diego Autoquestionnaire Version). The types of NTTM showed significant correlations with TCI and TEMPS-A. Results of the study support that NTTS is a reliable and valid scale.

Bu çalışmada, benlik mekanizmalarını dokuz kişilik tipi ile açıklayan Enneagram Sistemi'nin yeniden yorumlanması ile oluşturulan ve günümüzde geçerlik ve güvenirliği bilimsel açıdan kanıtlanmış bir ölçüm aracı bulunmayan Dokuz Tip Mizaç Modeli (DTMM) ile uyumlu bir ölçek geliştirilmesi amaçlanmıştır. 91 maddeden oluşan ve üçlü Likert tipi bir öz bildirim ölçeği olan Dokuz Tip Mizaç Ölçeği (DTMÖ) 990 üniversite öğrencisine uygulanmıştır. Ölçeğe uygulanan açıklayıcı faktör analizlerinde dokuz faktörün öz değerleri 8.08 ve 1.66 arasında değişmekte ve toplam varyansın %39.04'ünü temsil etmektedir. Ölçeğin modele uygunluğunu saptamak için doğrulayıcı faktör analizi uygulanmıştır. Ölçeğin doğrulayıcı faktör analizi sonuçlarına göre CFI değeri 0.88, GFI değeri 0.84, IFI değeri 0.88 ve RMSEA değeri 0.05'tür. Ölçeğin test-tekrar test güvenirliği 46 katılımcıyla sınanmıştır. Ölçeğin tümü için Cronbach alfa değeri 0.75, tipler için sırasıyla 0.77, 0.79, 0.68, 0.71, 0.80, 0.74, 0.71, 0.83, 0.77’dir. Ölçeğin eş zamanlı geçerliği Cloninger'in MKE (Mizaç ve Karakter Envanteri) ve Akiskal'in TEMPSA(Temparement Evaluation of Memphis, Pisa, Paris and San Diego- Autoquestionnaire) ölçekleriyle sınanmıştır. DTMM'deki tipler TCI ve TEMPS-A ile anlamlı bağıntılar göstermiştir. Araştırmanın sonuçları DTMÖ'nün geçerli ve güvenilir bir ölçek olduğunu desteklemektedir.
Dokuz Tip Mizaç Ölçeği'nin geçerlik ve güvenirliği
Keywords: Nine Types Temperament Model; Nine Types Temperament Scale; Reliability; Temperament; Validity; Mizaç; Dokuz Tip Mizaç Modeli; Dokuz Tip Mizaç Ölçeği; Güvenirlik; Geçerlik